UPAYA PENANAMAN NILAI AGAMA DAN MORAL PADA ANAK USIA 4-5 TAHUN - Ranggi paramitra; Nanik yuliati; Senny weyara dienda saputri (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to describe the teacher's efforts in instilling religious and moral values ​​in children aged 4-5 years in group A TK Dharma Wanita Tegal Gede Jember. The subjects of this study were teachers and children aged 4-5 years who were in group A. The type of research used was descriptive qualitative research. Methods of collecting data with non-participatory observation methods on teachers and children, semi-structured interviews with teachers and documentation related to the religious and moral values ​​of children at school. The results showed that efforts to instill religious and moral values ​​in children aged 4-5 years in group A were carried out by the teacher every day. In the implementation of the planting, the teacher is carried out in accordance with the teacher's role, namely as a teacher, mentor, and as a role model. Efforts to inculcate religious and moral values ​​also encountered obstacles so that the stimulation provided by the teacher was not optimal